The contradictory duals: The meaning and the term - Hassan, Khaled Abd alazaiz (Arab Journal for Sciences and Research Publishing, 2019)
The presence of existence on the binaries, was a feature of the main that left nothing but a problem for its features, and literature one of them; we find the diodes have intersected the joints, and formed its internal texture, and showed its purposes and themes in a striking way to the recipient who felt the beauty and beauty of rhythms and images express.Classical Arabic is characterized among all other semiotic languages; It's characteristics ate unique to them which reflected the prestige and ability for expression. Amongst these Fixed characteristics in Arabic language there is the contradictory duals.In this study, I tried to trace the terms "binary" and "contrast": language and language, and the approach between them to arrive at a single integration, forming another term " contradictory duals", and its role in the literary text on the one hand and on the receiver on the other hand.
Keywords: Critical Terminology; Antonyms; Dualism